Desenvolvimento conceitual de um motovibrador unidirecional utilizado em acionamento de chaves seccionadoras - Rodrigues, Huann Costa (2021)
In some occasions, the switches of the high voltage disconnect switch have not closed completely due the friction and electric arc which it causes large problems for the equipment and the electricity companies have to mobilize workers to the locations where there is need of the switches closing. Therefore, aiming to solve that problem, Rocha (2013) developed a model patent BR 10 2013 020198 7 which, according to him, when vibration is applied to the structure, it can reduce the strength of dry friction between the contacts and the stem and contribute it to close completely. Hence, the focus of this research is the conceptual development of a directional motovibrator applied in high voltage disconnect switch as Lorenzetti EV 242 kV and Harvey Hubble BMKU-40A. The directional motovibrator has to be fixed on the structure of the disconnect switch and it is studied too. The list of requirements developed by using the design methods of Pahl et al. (2005) guided the conceptual development. Twelve solutions achieved the global function of the product and a selection made possible to obtain four final varieties that resulted in a directional motovibrator and its mounting brackets. An innovative product obtained can produced vibration directional because of its eccentric masses that rotate in opposite directions. Three pulleys and one double-sided synchronous belt perform the transmission of movement. The final concept has a modular system to mount it on the structure and a fixed guard in accordance with the standards NR-12 and IP 66.